Position detection of guidewire tip emitting ultrasound by using a Kalman filter. (27th July 2021) - Takeshima, Hirozumi; Tanaka, Tomohiko; Imai, Ryo
Abstract: Echo-guided intervention is a promising minimally invasive surgery in the ultrasound (US) image guide because of its non-invasiveness and the high visuality of blood vessels. However, detecting the position of an intervascular device is difficult under an echo-guided intervention. To overcome this problem, we proposed a novel position detection method for an echo-guided intervention with a small photoacoustic transmitter. The method detects the position of the intervascular device by receiving the US that the transmitter at the device tip emits. Because its accuracy decreases under weak signal conditions, this paper proposes a Kalman filter-based filtering method to improve the accuracy of the position detection. The proposed filter reduces the detection error based on a linear approximation of the system. Our experiment shows the filter reduces 52% of the root mean squared error during position detection in an elevation direction.